Family Support And Exclusive Breastfeeding Among Working Mothers At The Hospital - Ummah, Faizatul; Sulistyaningsih, Sulistyaningsih; Rosida, Luluk (Universitas Aisyah Pringsewu, 2023)
Exclusive breastfeeding in developing countries is still low, especially among working mothers. This study aims to determine the relationship between family support and exclusive breastfeeding for working mothers in hospitals in the Lamongan district. The method in this study used a cross-sectional analytical research design, the sample was working mothers in the Lamongan district hospital who had babies aged 6-24 months and met the inclusion criteria, totaling 120 people using purposive sampling. Data collection was carried out in August–September 2022 using questionnaires, analyzed univariately, bivariate (chi-square), and multivariate (logistic regression). The results showed that family support was significantly related to exclusive breastfeeding (p 0.000; OR 13.8; 95% CI: 4.819-39.381). Maternal characteristics that were significantly associated with exclusive breastfeeding were parity (p 0.034; OR 2.999; 95% CI: 1.086-8.038) and employment (p 0.003; OR 3.76; 95% CI 1.513-9.357). Family support is the most dominant factor related to exclusive breastfeeding for working mothers in hospitals. Mothers who receive good family support have a 13.8 times chance of providing exclusive breastfeeding compared to working mothers who receive less family support. It is recommended for health workers to provide IEC to families to provide optimal support for working breastfeeding mothers.